FORMATION OF LEADERSHIP QUALITIES IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE CONDITIONS OF AN INSTITUTION OF HIGHER EDUCATION - Machynska, Nataliia; Blikhar, Viacheslav; Kuzior, Aleksandra (Socio-economic relations in the digital society, 2024)
The research is conducted in the article and theoretical and practical analysis of the characteristics of leadership and the substantiation of the psychological and pedagogical conditions for the formation and development of leadership qualities in students in the process of professional training in a higher educational institution. An analysis of various approaches to the interpretation of the concepts of "leader", "leadership", "leadership in education", and "educational leadership" is proposed; Based on the various definitions analyzed, he identifies the signs of student leadership: initiative, contact, sensitivity, goodwill, broad social and intellectual horizons, willingness to help, etc. It is noted that the concept of leadership is considered by scientists in such aspects as leadership as a mechanism for introducing innovative changes, leadership as a model of personality formation, and leadership as the spiritual mission of an individual. The results of a study conducted among students of the first (bachelor's) level of higher education of specialty 013 "Primary Education", which was conducted to study the state of formation of leadership qualities. future primary school teachers are presented and characterized. Empirical studies have shown that students systematize all leadership qualities into the following groups: organizational, communicative, perceptual, creative, and self-regulatory. It is noted that confirmation of the qualities of a leader in future primary school teachers involves the creation of appropriate favorable conditions that ensure that students’ activities are focused on the development of leadership motivation. The article defines and characterizes the necessary psychological and pedagogical conditions: the formation of the motivational and value sphere of a future teacher education specialist for impact on the process of increasing the level of personal professional development within the limits of future professional activity; the readiness of the university’s scientific and teaching staff to work with potential leaders; formation of practical leadership experience in the conditions of educational applicants undergoing various types of teaching practice; development and implementation of training sessions in the educational process of professional training of future specialists.
Keywords: leader; leadership in education; leadership qualities; professional training; psychological and pedagogical conditions